HEAVY METAL TOXICITY AND CHRONIC KIDNEY DISEASE IN SOUTHERN TAMIL NADU: CHALLENGES, MECHANISMS, AND PUBLIC HEALTH PERSPECTIVES (Asian Journal of Medical Research and Health Sciences, 2026)
Chronic Kidney Disease (CKD) represents a signiﬁcant global health burden, characterized by a progressive decline in renal function. While traditional risk factors such as diabetes and hypertension are well-established, the role of environmental pollutants, particularly heavy metals, in the etiology and progression of CKD is gaining increasing attention. This comprehensive review synthesizes current knowledge on the impact of heavy metal exposure on CKD, with a speciﬁc focus on ﬁndings from the Southern Tamil Nadu population. It delves into the mechanisms by which various heavy metals, including but not limited to arsenic, lead, cadmium, and mercury, exert nephrotoxic eﬀects, leading to cellular damage, glomerulosclerosis, and impaired renal function. The review also examines the prevalence of heavy metal exposure in susceptible populations, routes of exposure, and the challenges in establishing clear causal links due to the heterogeneity of environmental factors and population demographics. Furthermore, it discusses diagnostic approaches, potential therapeutic interventions, and the critical need for eﬀective management strategies to mitigate the adverse health outcomes associated with heavy metal-induced nephropathy. By integrating ﬁndings from recent studies and highlighting the unique context of Southern Tamil Nadu, this review aims to provide a deeper understanding of this complex public health issue and underscore the importance of environmental monitoring and public health interventions to prevent and manage CKD.